Experimental effect of injectable calcium phosphate cement on osteoporotic distal radius: resistance in a fall provoking a Colles’ fracture - Noirfalisse, C.; Poumarat, G.; Liverneaux, P. (European journal of orthopaedic surgery & traumatology, 2007)
Stating backgroundThe purpose of this work was to determine a possible change, after an injection of calcium phosphate cement, in the mechanical resistance of the distal radius in fractures often seen in osteoporotic patients.MethodsWe reproduced a Colles’ fracture on two anatomical subjects. Only one wrist per cadaver had been injected of calcium phosphate cement Cementek LV®. In this way, we compared the mechanical strength of a wrist injected and a wrist not injected.ResultsThis study shows that an injection of calcium phosphate cement to replace the trabecular bone in the radius is mechanically interesting in preventing fractures in osteoporotic patients if the cement completely fills the bone cavity.ConclusionsThe confined study permits us to show that the cement has mechanical resistance in compression much better than those found in the trabecular bone.